Pharmacological aspects of acute treatment glycoside intoxication - M. I. Sperling; E. G. Kruchinin; A. S. Gogolevsky (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Despite the active introduction of surgical treatments for cardiac pathology and new synthetic cardiotonic drugs, cardiac glycosides (CG) remain an important component of the pharmacological treatment of heart diseases. Moreover, interest in this group of drugs is only increasing with the discovery of new pharmacological effects, such as antitumor and antiviral. However, despite many years of experience, the issue of managing patients with symptoms of both acute and chronic poisoning with cardiac glycosides remains one of the leading ones. The literature review provides a brief historical outline of cardiac glycoside poisoning and comprehensively describes the pharmacokinetics and pharmacodynamics of this group of drugs. The clinical picture of intoxication is described. We analyzed modern ideas and limitations of using antidote therapy such as digoxin immune Fab-antibody fragments, as well as the features of pathogenetic and symptomatic treatment of patients with acute glycoside poisoning.